Penggunaan youtube bagi tujuan berkaitan agama dalam kalangan generasi muda Islam di Malaysia - Mohd Faisal, Mustaffa (2021)
The younger generation of Muslims is now using YouTube to obtain various religious-related information in their daily lives. However, there are questions that arise regarding the differences in the use of YouTube among the younger generation of Muslims with a background in Islamic studies and non-Islamic studies for the purpose of obtaining information related to religion. This study aims to identify the level of basic religious knowledge, use, and acceptance of YouTube as a medium to obtain information related to religion using the qualitative and quantitative approaches. The first phase involves 31 informants who were interviewed in a focus group to record the level of knowledge and implementation of religious principles and the type of information sought from YouTube. The second phase applies the unobtrusive method in the computer lab which aims to examine the content of basic religious information search sites that are often browsed by the younger generation of Muslims involving 74 respondents. The third phase, a questionnaire adapted from the Unified Theory of Acceptance and Use of Technology (UTAUT) involved 800 respondents and the data were analysed using the Partial Least Squares Structural Equation (PLS-SEM). The results of the first phase study found that the younger generation of Muslims with a background in religious and non-religious studies has basic knowledge nd implementation of the five pillars of Islam and the ability to search for religion-related information on YouTube. While the result of the second phase study showed that the younger generation of Muslims has the ability to search for religion-related information on YouTube. The finding of the third phase study showed that performance expectancy, effort expectancy and social influence have a significant relationship towards behavioural intention to use YouTube for religious purposes. While the facilitating conditions and behavioural intention have no significant relationship to the use YouTube for religious purposes. This study also shows that there is no difference between the use of YouTube for religious purposes among the younger generation with Islamic and non-Islamic studies background. This study can help various parties to use YouTube as a medium to disseminate and obtain information related to religion for the benefit of all.